Novel Microcrystal Formulations of Sorafenib Facilitate a Long-Acting Antitumor Effect and Relieve Treatment Side Effects as Observed With Fundus Microcirculation Imaging - Wang, Junxiao; Liu, Rui; Zhao, Yun; Ma, Zhenhu; Sang, Zejie; Wen, Zhenyu; Yang, Xueling; Xie, Hui (Frontiers in Oncology, 2021)
The tyrosine kinase inhibitors (TKIs), including sorafenib, remain one first-line antitumor treatment strategy for advanced hepatocellular carcinoma (HCC). However, many problems exist with the current orally administered TKIs, creating a heavy medical burden and causing severe side effects. In this work, we prepared a novel microcrystalline formulation of sorafenib that not only achieved sustainable release and long action in HCC tumors but also relieved side effects, as demonstrated by fundus microcirculation imaging. The larger the size of the microcrystalline formulation of sorafenib particle, the slower the release rates of sorafenib from the tumor tissues. The microcrystalline formulation of sorafenib with the largest particle size was named as Sor-MS. One intratumor injection (once administration) of Sor-MS, but not Sor-Sol (the solution formulation of sorafenib as a control), could slow the release of sorafenib in HCC tumor tissues and in turn inhibited the in vivo proliferation of HCC or the expression of EMT/pro-survival–related factors in a long-acting manner. Moreover, compared with oral administration, one intratumor injection of Sor-MS not only facilitated a long-acting antitumor effect but also relieved side effects of sorafenib, avoiding damage to the capillary network of the eye fundus, as evidenced by fundus microcirculation imaging. Therefore, preparing sorafenib as a novel microcrystal formulation could facilitate a long-acting antitumor effect and relieve drug-related side effects.